2022
DOI: 10.3389/fpubh.2022.960928
|View full text |Cite
|
Sign up to set email alerts
|

Association between trajectories of fasting plasma glucose and risk of osteoporosis in non-diabetic and diabetic populations

Abstract: IntroductionPrevious studies based on a single measure of fasting plasma glucose (FPG) showed an inconsistent conclusion about the association between FPG and osteoporosis risk. Not accounting for time-varying and cumulative average of FPG over time could bias the true relation between FPG and osteoporosis. Our study aims to investigate the association between the trajectories of FPG and osteoporosis risk for non-diabetic and diabetic populations.MethodsA total of 18,313 participants who attended physical exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Some studies, but not all, have shown that higher fasting blood glucose was associated with increased BMD and a reduced risk of osteoporosis in patients both with and without diabetes [ 21 , 25 , 26 ]. Considering the temporal trajectories of fasting plasma glucose, the relationship between fasting blood glucose and osteoporosis risk appears bidirectional.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, but not all, have shown that higher fasting blood glucose was associated with increased BMD and a reduced risk of osteoporosis in patients both with and without diabetes [ 21 , 25 , 26 ]. Considering the temporal trajectories of fasting plasma glucose, the relationship between fasting blood glucose and osteoporosis risk appears bidirectional.…”
Section: Discussionmentioning
confidence: 99%
“…One‐way ANOVA was used for comparisons between subgroups. The classification of initial FPG levels was defined as follows: (i) normal FPG (≤ 5.6 mmol/L) and (ii) elevated FPG (≥ 5.7 mmol/L) 19 . Mean changed FPG values were used to describe the change of blood glucose after follow‐up, which is calculated by subtracting the initial FPG level from the last FPG level.…”
Section: Methodsmentioning
confidence: 99%
“…The classification of initial FPG levels was defined as follows: (i) normal FPG (≤ 5.6 mmol/L) and (ii) elevated FPG (≥ 5.7 mmol/L). 19 Mean changed FPG values were used to describe the change of blood glucose after follow-up, which is calculated by subtracting the initial FPG level from the last FPG level. Multivariate logistic regression was used to analyze the relationship between H. pylori infection and elevated FPG after adjusting for confounding factors, and the odds ratio and 95% confidence interval (CI) were calculated.…”
Section: Assessment Of Covariates the Healthy Managementmentioning
confidence: 99%
“…When osteoporosis occurs in diabetes patients, fragility fractures become a primary concern, often leading to associated pain. These fractures can significantly impact the physical and mental well-being of patients 6 7 . While low BMD is consistently observed in T1DM, in T2DM bone mineral density is similar to or higher than in nondiabetic subjects.…”
Section: Introductionmentioning
confidence: 99%